Unpacking teacher quality: key issues for early career teachers - Flores, Maria Assunção (2019)
This chapter analyses - and deconstructs - the concept of teacher quality by looking both at international research literature and legal texts as well as at the perspectives of various stakeholders (head teachers, teachers and pupils).